Human Monkeypox Virus infection - junita br tarigan; Maulinda Putri; Sri Ulina Br. Purba; Franciscus Ginting (Institut Kesehatan Medistra Lubuk Pakam, 2025)
Monkeypox is a zoonotic disease. First, this infection was found in animals but has been widespread in humans and become a pandemic all over the world including Indonesia with different case fatality rates caused by monkeypox infection among the countries. Some clinical features caused by monkeypox infection are similar to other infections caused by chicken pox and other viruses. Treating and preventing monkeypox infection need holistic management among medical personnel.